Multiple Sclerosis First Presentation in a Child: Diffuse Motor Demyelinating Polyradiculopathy: Case Report - Magd Ahmed Kotb (Cairo University, Faculty of Medicine, Department of Pediatrics, 2024)
Multiple sclerosis is a mostly debilitating chronic demyelinating immune disease of the central nervous system that compromises quality of life within 10-15 years of onset. The clinical picture spectrum varies widely depending on the underlying pathogenesis of demyelination; the macrophage induced demyelination, antibody mediated against myelin proteins, T cell- mediated small vessel vasculitis and subsequent ischemia or cytokine mediated oligodendrocyte death. Axonal injury is limited to 5% of cases. Peripheral nerve demyelination is an exceptionally rare association of multiple sclerosis. We report a 9-year-old who developed bilateral lower limb weakness and loss of truncal support. Electromyography revealed demyelinating diffuse motor polyradiculopathy. He was diagnosed as Guillain-Barré syndrome and received intravenous immunoglobulins with no response. Magnetic resonance imaging of the brain and cervical spine revealed multiple cerebral and cerebellar foci of abnormal signal representing demyelination. He was diagnosed as multiple sclerosis and had a full recovery within 3 weeks from start of management by methylprednisolone. Peripheral demyelinating neuropathy may be the initial presentation of multiple sclerosis in a child.